Biosecurity perspectives of equestrian competition organizers in Ontario, Canada - Turcotte, Gabrielle K.; O’Sullivan, Terri L.; Spence, Kelsey L.; Winder, Charlotte B.; Greer, Amy L. (Frontiers in Veterinary Science, 2026)
BackgroundBiosecurity plays an important role in the prevention and control of infectious disease outbreaks in the equine population. With competition organizers responsible for implementing and upholding biosecurity requirements at competitions, it is important to understand the biosecurity landscape at these locations where Ontario horses commonly travel and interact in large group settings.ObjectivesThe objective of this study was to describe the perspectives, challenges and experiences of competition organizers of both sanctioned and unsanctioned events in Ontario, Canada regarding implementing equine biosecurity at competitions.Study designThis study used a qualitative content analysis in order to gather data describing the lived experiences of competition organizers.MethodsOf 53 invited participants, semi-structured, individual interviews were conducted virtually with 10 Ontario competition organizers in English disciplines (Eventing, Dressage, Hunter/Jumper). A qualitative, inductive coding method was used to analyze the interview data.ResultsInterviews resulted in two major categories: (i) biosecurity at competitions is a balancing act among other important considerations and (ii) there is a disconnect between groups that play key roles in biosecurity at competitions.Main limitationsThe recruitment process allowed for the possibility of introducing self-selection bias where some of the participants may have an existing interest in biosecurity, which may not be representative of all competition organizers. Individual interviews as well as the design of the interview guide helped to mitigate some potential for social desirability bias.ConclusionBiosecurity at equestrian competitions is a multifaceted issue that requires stakeholder input and buy-in to be successful. However, there is an overall willingness from competition organizers to work toward finding a path forward to improving biosecurity and maintaining equine health and welfare at competitions.